Lesby, gejki, postlesbijki. Konstrukcje tożsamości lesbijskiej w polskiej prozie najnowszej - Tarnowska, Małgorzata (Zagadnienia Rodzajów Literackich, 2024)
Lesbian identity is one of the central issues of lesbian studies since the 1990s. A reading of classic works by Tamsin Wilton, Celia Kitzinger, Tracy Morgan or Rosa Ainley shows that this category has been analyzed and viewed as deeply ambivalent all along: on the one hand suspicious in light of deconstructionist efforts to dismantle all essential identities, on the other, desirable as an important tool in the process of emancipation and overcoming patriarchal discourse with its inscribed drive to erase — to use Adrienne Rich’s term — lesbian existence. In Polish literature, especially in contemporary prose which interests me in this article, the question of this identity has become increasingly important over the past two decades with the increasing presence of queer women writers in the literary mainstream. While works from the late 20th and early 21st centuries focused mainly on highlighting and exposing mechanisms of its production by depicting “ordinariness” of lesbian life, works published today are distinguished by a markedly different attitude to gender and sexual identity. The subject of the article is an analysis of contemporary (21st-century) Polish prose in terms of ways in which lesbian identity is constructed, using two texts as examples: Moja ukochana i ja [My beloved and me] by Renata Lis and Nie wszyscy pójdziemy do raju [We will not all go to paradise] by Olga Górska. I will analyze the issue of the title in three areas. First, I will consider how the authors (born in 1970 and 1988, respectively) describe discourses (political, medical, cultural) on lesbianism that shape their texts’ narrators’ self-knowledge. Second, I will discuss how the authors describe themselves in relation to the category “lesbian,” linking it to contemporary intellectual discourses on lesbian and post-lesbian identity. Third, I will consider what prospects for queer solidarity in Poland are opened up by these opposing (as it will turn out) propositions.